2016
DOI: 10.1038/gim.2015.19
|View full text |Cite
|
Sign up to set email alerts
|

Patient feedback and early outcome data with a novel tiered-binned model for multiplex breast cancer susceptibility testing

Abstract: Original research article INTRODUCTION Multiplex (i.e., multigene) panels including both high-and moderate-penetrance cancer susceptibility genes are currently being used in clinical practice despite questions regarding their clinical utility and no standard approach to genetic counseling and delivery. [1][2][3][4][5][6] The inclusion of genes with varying penetrance and clinical utility has raised concerns. 7 There are both advantages and disadvantages of multigene testing (as opposed to traditional phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
121
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(127 citation statements)
references
References 43 publications
(62 reference statements)
5
121
1
Order By: Relevance
“…Bradbury et al found that previously tested BRCA1/2 negative patients were more likely to go forward with multiplex testing after tiered/binned counseling compared to BRCA1/2 untested patients (BradburyPatrick-MillerEgleston et al, 2015). Patients that received testing did not have significant changes in anxiety, depression, cancer worry and uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Bradbury et al found that previously tested BRCA1/2 negative patients were more likely to go forward with multiplex testing after tiered/binned counseling compared to BRCA1/2 untested patients (BradburyPatrick-MillerEgleston et al, 2015). Patients that received testing did not have significant changes in anxiety, depression, cancer worry and uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…For complex PGx tests, such as panelbased tests, laboratories could organize patient handouts and consent forms using a 'tiered and binned' approach that focuses on key themes rather than genespecific information [58]. Development of multiple 'tiers' of information to which providers may tailor discussions based on patient needs resulted in increased patient knowledge and patient-reported informed decision [59]. Similar approaches have also been proposed for personal genome testing [60].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that genetic counseling and more extensive knowledge shifted preferences toward a desire for less, rather than more genetic risk information (Bradbury et al, 2015; Middleton et al, 2016). Our study found similar shifts in the public’s policy preferences for the return of secondary genomic results, suggesting that in-depth education and peer deliberation may lead to a more nuanced (and sometimes more critical) view of the value of this type of information.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies have found that preferences shifted toward wanting less information when participants had more extensive knowledge, including that gained as a result of genetic counseling (Bradbury et al, 2015; Middleton et al, 2016). However, there are no in-depth studies of the views of the public after receiving balanced scientific and ethical information relevant to secondary genomic results.…”
Section: Introductionmentioning
confidence: 99%